First Principles Study of Copper Sulfides (for applications as photoconductors) - J. A. Ferreira (2013)
The Tetrahedrites family constitutes a complete solid-solution series, and is among the most frequent complex sulfides in Nature. This kind of structure can be generically expressed by the composition, Cu12Sb4S13. We have calculated the electronic band structure of Cu12Sb4S13 and Ag6Cu6Sb4S13 (with band gaps of 1.24 and 1.20 eV, respectively) to demonstrate that different elements occupying certain sites of the crystal structure will make a difference in what concerns the conduction process in Tetrahedrites. We will use this effect and ab initio calculations to show that the electronic properties of these compounds make them promising candidates as solar cells photovoltaic materials since not only they possess a direct band gap but their energy falls within the range of energies of photovoltaics. Moreover, we can optimize these properties by doping and substituting ions furthermore. Mechanical properties were also calculated for both compounds and will be compared.